Application of high shear-assisted liquid biphasic system for protein extraction from Chlorella sp - Silvanir, .; Lai, Sin Yuan; Azren Aida, Asmawi; Chew, Kit Wayne; Ngan, Cheng Loong (Elsevier, 2024)
Microalgae is a sustainable alternative source to traditional proteins. Existing pretreatment methods for protein extraction from microalgae still lack scalability, are uneconomical and inefficient. Herein, high shear mixing (HSM) was applied to disrupt the rigid cell walls and was found to assist in protein release from microalgae. This study integrates HSM in liquid biphasic system with seven parameters being investigated on extraction efficiency (EE) and protein yield (Y). The highest EE and Y obtained are 96.83 ± 0.47 % and 40.98 ± 1.27 %, respectively, using 30% w/v K3PO4 salt, 60 % v/v alcohol, volume ratio of 1:1 and 0.5 % w/v biomass loading under shearing rate of 16,000 rpm for 1 min.